Role of Health Literacy on Health Behaviour Change among the College Girl Students (Scholars' Journal, 2021)
Health literacy refers to a person's knowledge and abilities to make sound health decisions in everyday life. The overall goal of this study was to discover the influence of health literacy on the health behaviour of college girls, using proportionate stratified sampling, 178 (55.27% females studying health and physical education (HPE) at Surkhet Campus, and HA/Staff Nurse at SEDA Campus, Surkhet were chosen. Researchers used a cross-sectional design for this study. The Short Test of Functional Health Literacy in Adults (S-TOFHLA) was used to assess health literacy, while the Self-Administered Questionnaire was used to assess health behaviour. As per the survey findings, 53.93% of respondents had appropriate health literacy. Health literacy plays a key role in physical activity and its duration. Furthermore, study revealed that health literacy has no role on campus girls' smoking, using alcohol, and health check-up behaviour. Finally, the research suggested that health literacy is required to include in higher education programmes.